2018
DOI: 10.1152/jn.00113.2018
|View full text |Cite
|
Sign up to set email alerts
|

Using gaze behavior to parcellate the explicit and implicit contributions to visuomotor learning

Abstract: Successful motor performance relies on our ability to adapt to changes in the environment by learning novel mappings between motor commands and sensory outcomes. Such adaptation is thought to involve two distinct mechanisms: an implicit, error-based component linked to slow learning and an explicit, strategic component linked to fast learning and savings (i.e., faster relearning). Because behavior, at any given moment, is the resultant combination of these two processes, it has remained a challenge to parcella… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
111
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(132 citation statements)
references
References 59 publications
20
111
1
Order By: Relevance
“…Reducing shoulder muscle activity after shoulder fixation with instruction and feedback Many previous studies have investigated the role of explicit cognitive strategies in motor learning de Brouwer et al 2018;Christou et al 2016;Mazzoni and Krakauer 2006;McDougle et al 2015;Miyamoto et al 2020;Poh et al 2016;Rand and Rentsch 2015;Stark-Inbar et al 2017; . Regardless of the type of learning studied (i.e., visuomotor rotation, forcefield, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing shoulder muscle activity after shoulder fixation with instruction and feedback Many previous studies have investigated the role of explicit cognitive strategies in motor learning de Brouwer et al 2018;Christou et al 2016;Mazzoni and Krakauer 2006;McDougle et al 2015;Miyamoto et al 2020;Poh et al 2016;Rand and Rentsch 2015;Stark-Inbar et al 2017; . Regardless of the type of learning studied (i.e., visuomotor rotation, forcefield, etc.…”
Section: Discussionmentioning
confidence: 99%
“…We ask people to make open-loop reaches to targets after adaptation, while either using the strategy they just learned (implicit and explicit), or not using it (only implicit). We use this measurement task as it doesn't seem to evoke additional explicit learning itself, as other methods do (Leow et al, 2017;de Brouwer et al, 2018;Maresch and Donchin, 2019), and to keep results comparable to earlier work from our lab (Modchalingam et al, 2019). While explicit learning does not necessarily lead to external error attribution, it is likely that external error attribution is accompanied with more explicit adaptation.…”
Section: External Error Attribution Reduces Implicit Processesmentioning
confidence: 99%
“…The full effect of adaptation seen by Stratton (1896Stratton ( , 1897 and Kohler (1941Kohler ( , 1951aKohler ( , 1951b occurred following five full days of exposure. However, recent research has suggested that implicit adaptation remains stable over two days of training (de Brouwer et al, 2018;Huberdeau et al, 2019). This may be explained if it takes more than two days of exposure for fragile motor memories to transform into consolidated memories that are protected from disruption and more difficult to unlearn (Krakauer and Shadmehr, 2006;Criscimagna-Hemminger and Shadmehr, 2008; but see Caithness et al 2004).…”
Section: Introductionmentioning
confidence: 99%